What is the solution \( (a, c) \) to this system of linear equations? \( \begin{array}{l}2 a-3 c=-6 \\ a+2 c=11 \\ \left(-\frac{76}{7}, \frac{17}{7}\right) \\ (3,-4) \\ (3,4) \\ \left(\frac{87}{7},-\frac{5}{7}\right)\end{array} \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Mind Expander
To solve the system of equations, we can use substitution or elimination. We have two equations: 1. \( 2a - 3c = -6 \) 2. \( a + 2c = 11 \) From the second equation, we can express \( a \) in terms of \( c \): \[ a = 11 - 2c \] Now substitute \( a \) into the first equation: \[ 2(11 - 2c) - 3c = -6 \] \[ 22 - 4c - 3c = -6 \] \[ 22 - 7c = -6 \] Now, solve for \( c \): \[ -7c = -6 - 22 \] \[ -7c = -28 \] \[ c = 4 \] Now substitute \( c = 4 \) back into the equation for \( a \): \[ a = 11 - 2(4) \] \[ a = 11 - 8 \] \[ a = 3 \] Thus, the solution to the system of equations is: \( (a, c) = (3, 4) \) So the correct choice from the given options is \( (3,4) \).